Alcohol-Induced Neuroinflammatory Response and Mitochondrial Dysfunction on Aging and Alzheimer’s Disease - León, Brandon Emanuel; Kang, Shinwoo; Franca-Solomon, Gabriela; Shang, Pei; Choi, Doo-Sup (Frontiers in Behavioral Neuroscience, 2022)
Mitochondria are essential organelles central to various cellular functions such as energy production, metabolic pathways, signaling transduction, lipid biogenesis, and apoptosis. In the central nervous system, neurons depend on mitochondria for energy homeostasis to maintain optimal synaptic transmission and integrity. Deficiencies in mitochondrial function, including perturbations in energy homeostasis and mitochondrial dynamics, contribute to aging, and Alzheimer’s disease. Chronic and heavy alcohol use is associated with accelerated brain aging, and increased risk for dementia, especially Alzheimer’s disease. Furthermore, through neuroimmune responses, including pro-inflammatory cytokines, excessive alcohol use induces mitochondrial dysfunction. The direct and indirect alcohol-induced neuroimmune responses, including pro-inflammatory cytokines, are critical for the relationship between alcohol-induced mitochondrial dysfunction. In the brain, alcohol activates microglia and increases inflammatory mediators that can impair mitochondrial energy production, dynamics, and initiate cell death pathways. Also, alcohol-induced cytokines in the peripheral organs indirectly, but synergistically exacerbate alcohol’s effects on brain function. This review will provide recent and advanced findings focusing on how alcohol alters the aging process and aggravates Alzheimer’s disease focus on mitochondria function. Finally, we will contextualize these findings to inform clinical and therapeutic approaches towards Alzheimer’s disease.